Firm bankruptcies and start-up activity in Switzerland during the COVID-19 crisis - Florian Eckert; Heiner Mikosch (Swiss Journal of Economics and Statistics, 2022)
This paper examines the incidence of firm bankruptcies and start-ups in Switzerland based on unique register data. We propose to assess the frequency of bankruptcies over time using the concept of excess mortality. During the COVID-19 crisis in 2020 and the first half of 2021, bankruptcy rates were substantially lower as compared to the pre-crisis period. This holds across most industries and regions. The Great Recession and the Swiss Franc Shock showed reverse patterns. Bankruptcies dropped more in industries and cantons, in which the share of firms who received a COVID-19 loan is comparatively high. In winter 2021, bankruptcies rebounded strongly. Since summer 2020, the number of new firm formations has been significantly higher compared to the time before the crisis. This is also in contrast to the previous crises. The strong start-up activity is driven by industries where the pandemic induced structural adjustments.
Keywords: E32; G33; M13; 330; Canton-level; COVID-19 crisis; Excess mortality; Firm bankruptcies; Firm formations; Industry-level; Insolvencies; Start-ups; Switzerland